Reading Comprehension Question Levels in Grade X English Students’ Book in Light of the Issues of Curriculum Policy in Indonesia - Surtantini, Rin (Master Program in Linguistics, Diponegoro University, 2019)
This article aims at finding out the reading comprehension-question levels as constructed for some chapters of English Students’ Book for Grade X published in 2017 by The Ministry of Education and Culture of Indonesia. The data were taken purposively and analyzed using Barrett’s taxonomy of reading comprehension to examine the levels of comprehension questions provided in the book. While higher-order thinking skills (HOTS) in Bloom’s taxonomy involve students to analyze, to evaluate, and to create, Barrett’s reading comprehension levels exhibit corresponding features, namely inferential comprehension, evaluation, and appreciation. The analysis is to show the corresponse the reading comprehension questions in the book to the current issues of HOTS in the curriculum policy of Indonesia. The results demonstrate that while some of the comprehension questions (21%) comply with the higher level of reading comprehension, the rest (nearly 80%) show lower level of reading comprehension. In response to the implementation of the curriculum policy in Indonesia, teachers need to practice constructing higher levels of comprehension questions that considerably make students get used to think critically